1997
DOI: 10.1111/j.1365-2621.1997.tb15468.x
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Treatment of Milk and Effects on Microbiological and Sensory Quality of Cheddar Cheese

Abstract: The effect of cycled high pressure treatment of milk on the yield, sensory, and microbiological quality of Cheddar cheese was investigated. Cheddar cheeses were made from pasteurized, raw, or pressure treated milk according to traditional methods. Flavor scores from trained dairy judges were not different for pasteurized and pressurized milk cheeses (P≤0.05). Percent moisture and wet weight yields of pressure treated milk cheeses were higher than pasteurized or raw milk cheeses (P≤0.05). Microbiological qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 11 publications
3
40
2
3
Order By: Relevance
“…Furthermore, storage of milk after the HP treatment may influence the results as it leads to an increased moisture content of the curd (Huppertz et al, 2004h). Drake, Harrison, Asplund, Barbosa-Ca´novas, and Swanson (1997) found that Cheddar cheeses made from HP-treated milk (three 1-min cycles at 586 MPa) presented higher moisture contents than raw or pasteurized milk cheeses. This was responsible for higher cheese yields, and also for lower texture scores.…”
Section: Cheese Manufacture From High Pressure-treated Milkmentioning
confidence: 96%
“…Furthermore, storage of milk after the HP treatment may influence the results as it leads to an increased moisture content of the curd (Huppertz et al, 2004h). Drake, Harrison, Asplund, Barbosa-Ca´novas, and Swanson (1997) found that Cheddar cheeses made from HP-treated milk (three 1-min cycles at 586 MPa) presented higher moisture contents than raw or pasteurized milk cheeses. This was responsible for higher cheese yields, and also for lower texture scores.…”
Section: Cheese Manufacture From High Pressure-treated Milkmentioning
confidence: 96%
“…Increased curd yield can be obtained by HP treatment of milk at 300-400 MPa (Lopez-Fandino et al, 1996;Arias et al, 2000;Needs et al, 2000b). The yield of Cheddar cheese made from HP-treated milk (3 cycles of 1 min at 586 MPa) was ;7% higher than that from raw or pasteurised milk (Drake, Harrison, Asplund, Barbosa-Canovas & Swanson, 1997) while the yield of cheese from caprine milk treated at 500 MPa was ;5% higher than that from pasteurised milk (Trujillo, Royo, Guamis & Ferragut, 1999b).…”
Section: Introductionmentioning
confidence: 94%
“…To date, five different cheese varieties have been manufactured from HP-treated milk; Cheddar cheese (345-676 MPa) (Drake, Harrison, Asplund, Barbosa-Canovas, Swanson, 1997), goats milk cheese (500 MPa) (San Martín-González, Rodriguez, Gurram, Clark, Swanson, & Barbosa-Cánovas, 2007;Buffa, Guamis, & Trujillo, 2005;Trujillo, Royo, Ferragut, Guamis, 1999), reduced-fat cheese (400 MPa) (Molina, Dolores Alvarez, Ramos, Olano, & Lopez-Fandino, 2000), Queso-fresco cheese (400 MPa) (Sandra, Standford & Meunier Goddik, 2004) and Camembert cheese (500 MPa) (Linton, Mackle, Upadhyay, Kelly, & Patterson, 2008).…”
Section: Introductionmentioning
confidence: 99%